1996
DOI: 10.1210/endo.137.1.8536632
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized murine osteoblasts derived from BMP 2-T-antigen expressing transgenic mice.

Abstract: Osteoblast cell lines capable of undergoing bone formation in vitro would provide useful models for understanding gene expression during bone cell differentiation. To that end, transgenic mice were produced using a 2.9-kilobase bone morphogenetic protein 2 (BMP-2) promoter fragment, driving simian virus 40 T antigen as the transgene. The expression of simian virus 40 T antigen driven by the BMP-2 promoter immortalizes the cells. From the calvaria of the transgenic mouse, several osteoblastic cell lines were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 0 publications
2
63
0
Order By: Relevance
“…We have shown previously that BMP-2 autoregulates its expression during osteogenesis (29). This is one of the mechanisms by which BMP-2 maintains its sustained effect during osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…We have shown previously that BMP-2 autoregulates its expression during osteogenesis (29). This is one of the mechanisms by which BMP-2 maintains its sustained effect during osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 88%
“…Transfection and Luciferase Assay-The BMP-2-LUC reporter plasmid, in which the firefly luciferase gene is driven by a 2.7-kb 5Ј-flanking sequence of BMP-2 gene, has been described before (17,28,29). BMP-2-LUC reporter plasmid was cotransfected with different expression plasmids using LipofectAMINE Plus reagent as described (20,21,26,30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in stark contrast to the findings presented in a previous report by Hadfield et al [20], where HTRA1 was shown to impart a negative influence over mineralized matrix formation by mouse 2T3 osteoblasts. One possible explanation may lie within the fact that 2T3 cells are derived from transgenic mice overexpressing the simian virus 40 (SV40) T antigen and as such are immortalized [34]. The fact that HTRA1 gene expression is known to be significantly affected in SV40 transformed cells [35] would imply that modifications of the osteogenic status of these cells brought about by changes in HTRA1 expression and activity may not be truly representative of nonimmortalized, primary cells.…”
Section: Discussionmentioning
confidence: 99%